EDUCATIONAL ISSUES IN THE RESOCIALIZATION PROCESS OF CRIMINAL OFFENDERS - Djubina, Jeļena; Vilks, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The primary focus of the research is to investigate educational challenges in the process of resocializing individuals with criminal tendencies. The research aims to analyze educational issues in the resocialization process of offender to facilitate a more effective resocialization of criminally inclined individuals into society. The research tasks encompass various key objectives, including the analysis of offender characteristics, exploration of the formation process of offender personalities, formulation of proposals to mitigate the negative impact of macro-environmental factors, and development of resocialization recommendations. The novelty of the research is linked to changes in cultural values and social norms influencing the behavior, motivation, and transformation of social values among criminally inclined individuals. The outcomes of the research will contribute to the development of more effective strategies for crime prevention and the resocialization of offender personalities within society. The chosen research methods will provide a comprehensive insight into the formation of offender personalities and the factors influencing them. The monographic method will be utilized to describe existing research findings and provide conceptual explanations regarding offender personality and its formation mechanisms. The comparative method will be applied to assess issues related to the prevention of criminal activities among criminally inclined individuals in Latvia and other countries.